Utilization of sodium carbonate activator in strain-hardening ultra-high-performance geopolymer concrete (SH-UHPGC) - Lao, Jian-Cong; Xu, Ling-Yu; Huang, Bo-Tao; Zhu, Ji-Xiang; Khan, Mehran; Dai, Jian-Guo (Frontiers in Materials, 2023)
In this study, strain-hardening ultra-high-performance geopolymer concrete (SH-UHPGC) was produced using Na2CO3, Na2SiO3 and their hybridization (1:1 in mole ratio) as alkaline activators. An ultra-high compressive strength was achieved for all the developed SH-UHPGC (i.e., over 130 MPa). SH-UHPGC with hybrid Na2CO3 and Na2SiO3 activators showed the highest compressive strength (186.0 MPa), tensile strain capacity (0.44%), and tensile strength (11.9 MPa). It should be highlighted that very significant multiple cracking can be observed for all the SH-UHPGC, even at a very low tensile strain level (e.g., 0.1 %). According to the reaction heat, microstructures, and chemical composition analyses, SH-UHPGC with hybrid activators had the highest reaction degree, while that of Na2CO3-based SH-UHPGC was the lowest. It was found that the Na2CO3-based SH-UHPGC showed the best sustainability, and the SH-UHPGC with hybrid Na2SiO3 and Na2CO3 presented the best overall performance (considering the mechanical properties, energy consumption, environmental impact, and economic potential). The findings of this work provide useful knowledge for improving the sustainability and economic potential of SH-UHPGC materials.